The Formalisation Of Social Engagement In The Medical Relief Ngo: The Evidence Of Mercy Malaysia - Abdul Aziz, Norazita Marina (Asian Academy of Management (AAM), 2016)
Social engagement involves the participation of a group people in undertaking collective activities in social community. The paper aims to examine the formalisation of NGO social engagement to their stakeholders. The MERCY's social engagement is not only focusing on the traditional forms of reports i.e. social reports to the stakeholders but includes the forms of actions including conversation, behavioural explanations and reasonable conduct through negotiation of performance and impact among stakeholders. The social engagement paradigm emphasises on the rights and contracts between two parties (i.e. Accountor and Accountee). The qualitative research is employed by undertaking empirical case study research for MERCY, an international disaster relief NGO that highlight an understanding of social engagement through the power of negotiation. The data are gathered through indepth series of interviews and documentary reviews, which was analysed through thematic analysis. The fndings revelas the social "closeness" within the community can be seen from the moral values imperatives that had driven by the trustworthiness and willingness of the people in the community to engage in the volunteering work.